2009
DOI: 10.1038/emboj.2009.378
|View full text |Cite
|
Sign up to set email alerts
|

mNUDC is required for plus-end-directed transport of cytoplasmic dynein and dynactins by kinesin-1

Abstract: Lissencephaly is a devastating neurological disorder caused by defective neuronal migration. The LIS1 (or PAFAH1B1) gene was identified as the gene mutated in lissencephaly patients, and was found to regulate cytoplasmic dynein function and localization. In particular, LIS1 is essential for anterograde transport of cytoplasmic dynein as a part of the cytoplasmic dynein-LIS1-microtubule complex in a kinesin-1-dependent manner. However, the underlying mechanism by which a cytoplasmic dynein-LIS1-microtubule comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 45 publications
5
57
1
Order By: Relevance
“…We previously demonstrated that LIS1 arrests dynein motility (Fig. 1a: lanes 1 and 2, Supplementary Movies 1 and 2) and that kinesin-1 transports a LIS1-dynein-tubulin complex to plus ends of MTs via mNUDC 9,10 . Before dynein can function as a retrograde motor, idling dynein must be activated to bind cargoes.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that LIS1 arrests dynein motility (Fig. 1a: lanes 1 and 2, Supplementary Movies 1 and 2) and that kinesin-1 transports a LIS1-dynein-tubulin complex to plus ends of MTs via mNUDC 9,10 . Before dynein can function as a retrograde motor, idling dynein must be activated to bind cargoes.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, Yamada et al (2010) demonstrated that, in cultured neurons, kinesin-1 binds and transports "transportable microtubules" (tMTs) via mammalian nuclear distribution gene C homolog (mNUDC). These tMTs act as carriers to transport cytoplasmic dynein.…”
Section: Discussionmentioning
confidence: 99%
“…nudA, nudF and nudE encode dynein HC, LIS1 and NDEL/ NDE1, respectively. Mammalian NUDC is required for kinesin-1-mediated anterograde transport of dynein 39 . Presumably, mutation of LC8 will lead to impairment not only of the unloading of cargoes but also dynein recycling.…”
Section: Discussionmentioning
confidence: 99%